DESAIN STRATEGI “BARCA STYLE” DAN RESPON PEMAIN PADA SIMULASI PERMAINAN SEPAK BOLA MENGGUNAKAN ALGORITMA KUCHIYOSE - Didik Kurniawan; Wamiliana Wamiliana; Afdi Patria (Jurnal Komputasi, 2013)
Nowadays, football is not just a sport performed by humans. The development of football has offered a variety of integration technologies in diverse of forms such as ball type, shoes, games, etc. The game that associated with football is now in a great demand by many people, such as PES 2013. Football game needs game strategies that determine the success of the game. Recently, one of the great team that has won numerous competitions is Barcelona FC. This club has interesting features and powerful enough to win the game. The unique feature is 'Barca style', which is the short passing between players. Basically there are three main roles in the game of football which are the player who controlled the ball, a player that supports the movement of the player who had the ball, and the opposing player trying to snatch the ball. In order to find solutions to address the characteristics of the ‘Barca Style’ we represent the game as mathematical model and design a simulation that uses a strategy game guarding one on one, and the total survival strategy against the strategy of 'Barca style'.